Weberian Civil Service and Labor Enforcement - Matías Dewey; Lucas Ronconi (Institute of Labor Economics (IZA), 2023)
Most workers in the developing world do not receive the benefits they are legally entitled to. Why, then, is there so little public enforcement? This paper argues that this is partly because of a lack of an autonomous and professional bureaucracy. Using a novel dataset with objective measures of labor inspections and fines across countries, we show that Weberian bureaucracies are more likely to enforce labor standards. We provide OLS and 2SLS estimates that address endogeneity concerns and use ethnographic evidence collected in Latin America to understand the mechanisms better. The case study suggests that politicized bureaucracies underinvest in labor inspection because elected officials have short-term horizons and do not internalize the social benefits of enforcement (such as formal job creation and enhancement of the rule of law) because they take time to materialize.
Keywords: J88; K42; O17; P50; 330; enforcement; autonomy; compliance; state-capture; labor